Reproductive Performance of Kacang Goats in Closed Population Areas of Sidoarjo Regency, East Java, Indonesia - Fitria Ella Wardani; Desinta Wulandari; Inggita Leli Murtika; Ahmad Furqon; Wike Andre Septian; Tri Eko Susilorini; Suyadi Suyadi (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
The objective of this study was to determine the reproductive performance of Kacang goats in a closed population area of Oro-Oro Farm located in Sawohan Village, Buduran Subdistrict, Sidoarjo Regency. We used 146 Kacang goat with a range of parity from 1 to > 7. Data analysis was carried out using the ANOVA test, Least Significant Difference (LSD) test, coefficient of variation test and descriptive test to measure litter size, pre-weaning mortality, kidding interval (KI), days open (DO) and Kacang goat reproduction index. The results showed that the highest litter size was 1.69 ± 0.63 at parity 6, the lowest pre-weaning mortality at parity > 7 was 11.76%, the shortest kidding interval and days open was at parity 4 for 7.35 ± 1.22 and 2.35 ± 1.22 months, respectively. The best Kacang goat reproduction index was 2.22 at parity 6 with coefficient of variation of 38.06%, 41.08% and 13.36% for litter size (LS), days open (DO), kidding interval (KI). Conclusively, there was a diverse reproductive performance of Kacang goats in the closed population area of Oro-Oro Farm located in Sawohan Village, Buduran Subdistrict, Sidoarjo Regency based on parity 1 to > 7, in which the higher the parity, the higher the reproductive performance. However, parity 5 onwards saw a declining reproductive performance due to weakened livestock conditions.